Legal Legalization of Online Buying and Selling Transactions - Fahrurrazi Hamim (IHSA Institute, 2022)
The purpose of this study is to analyze the legalization of the law regarding online buying and selling transactions. This research method uses qualitative sourced from secondary data. The results of this study indicate that Islam with all its norms and provisions continues to play with various advances and is able to position itself in the midst of rampant online transactions while still referring to the pillars and conditions of buying and selling that are fulfilled so that there is no abuse in transactions, e-commerce from various good reviews contained in positive law or Islamic law states that it is permissible and legitimate to do so by prioritizing the pillars and conditions that must be met. Online transactions, which we still consume today, have become an important forum for millennial life in its implementation while maintaining stability so that conflicts do not occur which lead to a lack of validity. Buying and selling, which was originally quite classic and a little complicated, has now turned into something that is instant and easy for us to implement and run systematically.